2020
DOI: 10.1080/13632434.2020.1719400
|View full text |Cite
|
Sign up to set email alerts
|

Giving voice to problems faced by school leaders in Portugal

Abstract: Worldwide, leadership stories are narratives of principals facing very different problems. The purpose of this study was to identify the current problems faced by Portuguese school principals, through these actors' voice. Nineteen public school Portuguese principals participated in this study. Semi-structured interviews were conducted, transcribed, coded, and categorised using Nvivo11 Pro. The analysis revealed that Portuguese principals have the same problems as their colleagues worldwide, but there are probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…Moreover, another study conducted found that Portuguese principals face challenges concerning the distribution of leadership and technical problems of the function, such as financial management with low resources and managing time between administrative and management tasks, and instructional leadership for learning tasks [57]. However, in this study, the distribution of leadership is not very expressive, and the management skills are quite expressive.…”
Section: Research Questions' Overviewmentioning
confidence: 64%
“…Moreover, another study conducted found that Portuguese principals face challenges concerning the distribution of leadership and technical problems of the function, such as financial management with low resources and managing time between administrative and management tasks, and instructional leadership for learning tasks [57]. However, in this study, the distribution of leadership is not very expressive, and the management skills are quite expressive.…”
Section: Research Questions' Overviewmentioning
confidence: 64%
“…Previous studies report on some critical aspects; a significant element in the teachers' working environment is the principal's leadership [7,8]. According to a study of Portuguese principals, problems arising from the process of school clustering and the leader-centered style of school management have always been a source of concern for the dysfunctional educational system [70]. Principals and teachers work together to create a school climate that promotes order, engages parents, and encourages student learning [28].…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is no single definition of "contingency" in educational terms, a part of the literature on leadership in general (Brinck and Tanggaard, 2016) and on instructional JEA 61,1 leadership (Davies, 2002) has described leadership as a difficult to predict process, in which acceptance and management of the unexpected is a condition for its effectiveness. A significant part of the actions and exchanges occurring at schoolsand in which a leading role by leaders is expectedare responses to "emerging problems" (Espuny et al, 2020), and therefore, are difficult to be planned (Ronnstrom and Skott, 2019). This kind of literature acts like a counterpoint to the traditional discussion about leadership, which tends to prescribe what leaders "should do" to impact student learning (Augustinsson et al, 2018) and putting instead more emphasis on how leaders manage conflict, process educational micropolitics (Johnson, 2004) and cope with the multiple unforeseen tasks occurring during the educational process (Christie and Lingard, 2001).…”
Section: Conceptual Framework: Complexity and Contingency School Lead...mentioning
confidence: 99%
“…Even though national and local contexts are determinants in the extent and type of problems faced by school leaders (Drago and Maslin, 2018;Oplatka, 2018;Tamadoni et al, 2021), research has also identified some problems that tend to be common, most of which arise emergent or unplanned (Clarke and Wildy, 2004;Espuny et al, 2020). These problems also tend to be more complex and recurrent in schools working under challenging circumstances (Harris, 2006;Gurr and Drysdale, 2018) and range from solving situations related to the instructional process to managing demands coming from the school environment (Day et al, 2020;Leithwood et al, 2020a).…”
Section: Conceptual Framework: Complexity and Contingency School Lead...mentioning
confidence: 99%
See 1 more Smart Citation